Lung arginase expression and activity is increased in cystic fibrosis mouse models - Jaecklin, Thomas; Dürr, Julia; Huang, Hailu; Rafii, Mahroukh; Bear, Christine E.; Ratjen, Felix; Pencharz, Paul; Kavanagh, Brian P.; Mall, Marcus A.; Grasemann, Hartmut (Journal of applied physiology, 2014)
The activity of arginase is increased in airway secretions of patients with cystic fibrosis (CF). Downstream products of arginase activity may contribute to CF lung disease. We hypothesized that pulmonary arginase expression and activity would be increased in mouse models of CF and disproportionally increased in CF mice with Pseudomonas aeruginosa pneumonia. Expression of arginase isoforms in lung tissue was quantified with reverse transcriptase-PCR in naive cystic fibrosis transmembrane conductance regulator (Cftr)-deficient mice and β-epithelial sodium channel-overexpressing [β-ENaC-transgenic (Tg)] mice. An isolated lung stable isotope perfusion model was used to measure arginase activity in Cftr-deficient mice before and after intratracheal instillation of Pseudomonas aeruginosa. The expression of arginase-2 in lung was increased in adult Cftr-deficient animals and in newborn β-ENaC-Tg. Arginase-1 lung expression was normal in Cftr-deficient and in newborn β-ENaC-Tg mice, but was increased in β-ENaC-Tg mice at age 1, 3, and 6 wk. Arginase activity was significantly higher in lung (5.0 ± 0.7 vs. 3.2 ± 0.3 nmol·−1·h−1, P = 0.016) and airways (204.6 ± 49.8 vs. 79.3 ± 17.2 nmol·−1·h−1, P = 0.045) of naive Cftr-deficient mice compared with sex-matched wild-type littermate controls. Infection with Pseudomonas aeruginosa resulted in a far greater increase in lung arginase activity in Cftr-deficient mice (10-fold) than in wild-type controls (6-fold) (P = 0.01). This is the first ex vivo characterization of arginase expression and activity in CF mouse lung and airways. Our data show that pulmonary arginase expression and activity is increased in CF mice, especially with Pseudomonas aeruginosa infections.